Keragaman Koloni Bakteri Indigenous Pengolahan Limbah Cair Industri Penyamakan Kulit - Wardani, Aisyah; syauqi, ahmad; Santoso, Hari (FMIPA - UNIVERSITY ISLAM OF MALANG, 2015)
Tanning industry waste is potential to pollute the environment because it is using a Â harmful chemical materials. One of many effort to prohibit the environmental pollution is a bioremediation using bacteria because bacteria can grow and adapt to any subtrats that has a organic materials. The diversity of bacteria is important to know because the bacteria covers most large species diversity on earth and its role as bioremediation. The purpose of Â this research is to determine the value of the diversity index and the types of indigenous gram bacteria in waste water Leather Tanning Industry Malang. Data has been analyzed results of measurements of pH, temperature, conductivity, the number of Â bacteria colonies, bacterial community structure (diversity, evenness, richness and dominance) and the results of bacterial gram staining.Diversity of indigenous bacteria colonies that has been found are low and the value is 0,36; 1,30 and 0,015. Type of indigenous gram bacteria found are streptococci negative (11%), streptococci positive (34%), Streptobacilli negative (11%), streptobacilli positive (34%), coccus negative (5%) and coccus positive (5%). Keywords:Diversity, Gram Strain, Bacteria, Waste Water, Tanning Industry